Integrated reports: disclosure level and explanatory factors. Issue 1 (6th March 2017) - Rivera-Arrubla, Yaismir Adriana; Zorio-Grima, Ana; García-Benau, María A.
Abstract : Purpose: This paper aims to look into the new corporate reporting phenomenon, the so-called integrated reporting (IR), so as to assess the information level provided, identify trends and explore its determining factors. Design/methodology/approach: This study looks into the IR disclosure level of the annual reports published by 91 companies in the International Integrated Reporting Council (IIRC)'s pilot programme. The authors' empirical research focuses on four areas: the guiding principles of connectivity and materiality, as well as two content elements: the business model and governance. Following extant research on voluntary disclosure, a disclosure index is proposed and some hypotheses are put forward on its connection with some corporate variables. Findings: The results point out that the disclosure levels of the IRs published by IIRC's pilot programme members reach medium levels of disclosure. According to the authors' index, the level of disclosure is significantly associated with the specific environment of organizations (i.e. region and industry), assurance of the report and publication in the IIRC website. Originality/value: This study makes a relevant contribution, as it presents an innovative IR disclosure index and sheds some light on the disclosure practices of early adopters of IR. This evidence is valuable in understanding the trends in this field and could help the IIRC and other standard setters with a view to improving sustainable development and reporting.